Accounting Management in Facing the Challenges of the Digital Economy (Maneggio, 2024)
The development of the digital economy has created a complex business ecosystem, demanding a rapid response from various parties, including accounting management. In this era, digital transformation is not just about adopting new technologies, but also a paradigm shift in financial information management. Technologies such as cloud accounting, big data analytics, and artificial intelligence are becoming an urgent need to ensure companies remain competitive. However, the implementation of these technologies faces challenges such as data security, workforce readiness, and high investment costs. In addition, digital transformation requires the ability to transform financial data into strategic insights, where accounting plays a role as a partner that can add value through predictive analysis and data-driven decision-making. This shift also requires accounting management to maintain a balance between information transparency and personal data security. Using a descriptive-analytical qualitative method, this study explores how companies adopt digital technology in accounting management and its impact on strategic decision-making. The results show that although digital transformation presents great opportunities, challenges such as data security, workforce training, and harmonization of accounting standards with technological developments must be managed well to create an efficient and sustainable accounting system in the digital era.